The role of agriculture in development: Implications for Sub-Saharan Africa - Diao, Xinshen; Hazell, Peter B. R.; Resnick, Danielle; Thurlow, James (International Food Policy Research Institute, 2007)
This report provides a nuanced perspective on debates about the potential for Africa’s smallholder agriculture to stimulate growth and alleviate poverty in an increasingly integrated world. In particular, the paper synthesizes both the traditional theoretical literature on agriculture’s role in the development process and discusses more recent literature that remains skeptical about agriculture’s development potential for Africa. In order to examine in greater detail the relevance for Africa of both the “old” and “new” literatures on agriculture, the paper provides a typology of African countries based on their stage of development, agricultural conditions, natural resources, and geographic location... More broadly, the paper demonstrates that conventional theory on the role of agriculture in the early stage of development remains relevant to Africa. While the continent does face new and different challenges than those encountered by Asian and Latin American countries during their successful transformations, most African countries cannot significantly reduce poverty, increase per capita incomes, and transform into modern economies without focusing on agricultural development.